(untitled) (Revista Repique, 2023)
The objective of this research is to provide an alternative solution through 3D printing of the handle of the glass elevator of the Chevrolet Aveo vehicle, which was simulated and evaluated in Inspire software where its mechanical properties were verified prior to printing. The 3D printing process was performed, and the weights of the original and optimized handle were compared with Inspire and Simsolid software, respectively. In addition, the displacements, safety factor, and deformation analysis of the original and optimized handle were compared. The study was based on the multi-criteria and COPRAS methods, to compare materials selected as the best alternatives to replace the original (PLA, PC and PVC). The results showed that the most suitable material to replace the original is PLA because it has excellent mechanical and physical characteristics. Through Inspire it was possible to change the original design of the handle, obtaining an optimized proposal with a 2.7% lower weight, in addition, the 3D printing time is reduced by 8.3% compared to the original model. With the present study it can be mentioned that the PLA alternative material is ideal to replace the original ABC-PC, and the benefits of the analysis contribute to have an alternative to industrial production in the world of vehicles.